1991
DOI: 10.1038/sj.bdj.4807548
|View full text |Cite
|
Sign up to set email alerts
|

Lasers in dentistry

Abstract: Clinical lasers are of two types; soft lasers are essentially an aid to healing with relatively few rigorous studies available to support their use. Surgical hard lasers, however, can cut both hard and soft tissues and replace the scalpel and drill in many areas. From initial experiments with the ruby laser most clinicians are using Argon, CO2 and now NdYAG systems. The first dental laser based on a NdYAG engine provides handpieces of similar size to conventional instrumentation and, being fed by a fibre-optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
16

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 0 publications
1
46
0
16
Order By: Relevance
“…Methods of killing periodontal pathogens, therefore, are of great interest and considerable attention has been devoted to the possibility of using antibiotics or antiseptics in this respect. More recently, it has been suggested that highpower lasers, such as Nd/YAG laser, which emit light in the infrared region may be useful for destroying such organisms, presumably by a thermal effect [8]. However, the clinical use of such high-power lasers introduces problems from the point of view thermal side effects on surrounding tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Methods of killing periodontal pathogens, therefore, are of great interest and considerable attention has been devoted to the possibility of using antibiotics or antiseptics in this respect. More recently, it has been suggested that highpower lasers, such as Nd/YAG laser, which emit light in the infrared region may be useful for destroying such organisms, presumably by a thermal effect [8]. However, the clinical use of such high-power lasers introduces problems from the point of view thermal side effects on surrounding tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Laser application adjunctive procedures have been described in several studies [7][8][9][10][11]. In a previous study [3], we tested the anesthetic effect of Nd:YAG laser irradiation on the gingival surface and evaluated pulpal blood flow rate and pulpal responsiveness during Nd:YAG laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“… It increases the formation of a secondary dentin by the odontoblasts (24) (25)  It obliterates the dentin tubules (26) …”
Section: Mechanism Of Action Of Lasersmentioning
confidence: 99%